2020
DOI: 10.1186/s12879-019-4736-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antifungal susceptibility of Candida albicans causing vaginal discharge among pregnant women in Lebanon

Abstract: Background Vaginal candidiasis is frequent in pregnant women and is associated with sepsis and adverse neonatal outcomes. This study determined the prevalence of candida species in symptomatic pregnant women and evaluated the antifungal susceptibility profile of the isolated Candida strains. It also aimed to explore whether Candida species predicts gestational complications and adverse neonatal outcomes. Methods A total of 258 pregnant women with v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 41 publications
2
32
0
9
Order By: Relevance
“…In addition, Ghaddar et al revealed that 97.5% of C . albicans isolates from VVC patients were resistant to VRC [ 37 ]. Our findings demonstrated that 23.4% and 10.6% of C .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ghaddar et al revealed that 97.5% of C . albicans isolates from VVC patients were resistant to VRC [ 37 ]. Our findings demonstrated that 23.4% and 10.6% of C .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, C. albicans infections pose a serious public health threat worldwide including Lebanon. To date only a handful of studies have addressed resistance of Lebanese C. albicans isolates to azoles, echinocandins, and polyenes [11–17] but none of the studies have looked at the entire genome of C. albicans to generate a complete picture of the genomic aspects of antifungal resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive candidiasis for instance is estimated to affect more than 250 million people causing more than 50,000 deaths worldwide every year. Epidemiological data unveils an incidence of 2 to 14 cases of candidemia per 100,000 individuals with a mortality range of 10 to 20% (Ghazi et al, 2019).Such infections occur as opportunistic consequences of other health problems including surgical operations, asthma, malnutrition, AIDS, cancer, alcoholism, organ transplantation, diabetes, corticosteroid therapies and the widespread drug resistance (Nowak and Szyfter, 2008;Tudela and Denning, 2017;Bongomin et al, 2017;Ghaddar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%